The initiation of the second-step intradisciplinary tumor board discussion and its impact on treatment decision. Retrospective data analysis of 12 years’ experience in a tertiary oncology center - Mangel, László Csaba; Kövér, Erika; Pécsi, Balázs; Boncz, Imre (Frontiers in Oncology, 2025)
BackgroundMultidisciplinary team (MDT) meetings are generally accepted forums for the quality of cancer care, however, there is an ongoing discussion about the substantial role of MDTs in reaching optimal treatment decisions. In our tertiary oncology center, a second-step intradisciplinary seu oncotherapy tumor board (OTT) discussion system was introduced to increase the adherence of MDT’s decision making with the knowledge of patients’ preference and tolerance, and to partially relieve MDT’s overwork in the purely adjuvant and the palliative treatment settings. Over the real-world tumor board data elaboration, the primary aim of this observational study was to present the impact of OTT meetings on treatment decisions.MethodsThe data of 33,056 cases of 27,227 patients were retrospectively analyzed with using a regular expression-based word search algorithm. Subsequent modifications of OTT decisions were defined as “minor”, when only some additional suggestions were introduced, “moderate” when the treatment items were significantly modified, and “major” when the direction of the treatment was fully transformed.ResultsDuring the 12-year observation period (2007-2019) the number of patients and case discussions, average age of the patients, percentage of sophisticated treatment methods, and the number of treatment lines/decisions made for the same patient had been continuously increased. The average percentage of minor, moderate and major modifications were 2.28, 6.4 and 8.92%, respectively, implying a remarkably high modification rate of the primary recommendations.ConclusionConsidering the growing complexity and multiplicity of oncology care, regular OTT board meetings can increase the accuracy of MDT’s work and treatment decisions without any overwork of the related disciplines and can also serve as an additive/alternative teamwork forum in the adjuvant, multiple line, and palliative care settings.